2002
DOI: 10.1046/j.1365-2788.2002.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenging behaviour and insecure attachment

Abstract: These preliminary results justify more detailed and longitudinal research into the relationship between attachment status and challenging behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 7 publications
(6 reference statements)
5
33
1
1
Order By: Relevance
“…The stress-attachment model, devised by Janssen et al (2002), suggests that challenging behaviour in thiis group serves a regulatory function for high levels of stress. This, in some ways, is an extension of the view that challenging behaviour is a protest response that aims to establish contact with the secure regulatory base (Clegg and Lansdall-Welfare, 1995;Clegg and Sheard, 2002). Furthermore, the despair phase of separation can be characterised by loss of abilities, loss of appetite and complete withdrawal.…”
Section: Separation Responses Of People With Profound Learning Disabimentioning
confidence: 99%
See 1 more Smart Citation
“…The stress-attachment model, devised by Janssen et al (2002), suggests that challenging behaviour in thiis group serves a regulatory function for high levels of stress. This, in some ways, is an extension of the view that challenging behaviour is a protest response that aims to establish contact with the secure regulatory base (Clegg and Lansdall-Welfare, 1995;Clegg and Sheard, 2002). Furthermore, the despair phase of separation can be characterised by loss of abilities, loss of appetite and complete withdrawal.…”
Section: Separation Responses Of People With Profound Learning Disabimentioning
confidence: 99%
“…The prevalence of separation anxiety is therefore higher than in their typically developing peers (Emerson, 2003). A weaving of interactional factors may give rise to this, including affect dysregulation, psychopathology (Schuengel et al, 2006) and insecure attachment relationships (Clegg and Sheard, 2002;Clements and Barnett, 2002). This combination, within the wider context of societal and cultural issues affecting people with LD, is believed to contribute to significant difficulties with loss experiences (Blackman, 2016).…”
Section: Attachment and Learning Disabilitiesmentioning
confidence: 99%
“…Most young children want to please the significant adults in their lives starting with their parents. The parent-student relationship forms the basis for the teacher-student relationship (Clegg & Sheard, 2002;Venet, et al, 2007).…”
Section: Parentsmentioning
confidence: 99%
“…The active participation of parents in meetings and acknowledgment of their children's assets and achievements increases the value of the program to students (Clegg & Sheard, 2002;Pogoloff, 2004;Venet, et al, 2007). programs at either the intervention or home school.…”
Section: Parental Input and Interestmentioning
confidence: 99%
“…Huebner and Thomas (1995) found evidence that if children with developmental delays had insecure attachments to their mothers, they were two to four times more likely to show psychopathology later in life. Likewise, Clegg and Sheard (2002) found that children and adults with intellectual disabilities who had insecure attachments with their parents were more likely to exhibit challenging behaviors, and Wellemsen-Swinkels, Bakermans-Kranenburg, Buitelaar, Van IJzendoorn, and England (2000) found that children with pervasive developmental disorders who had secure attachments scored higher on measures of social skills.…”
Section: Attachment In Children With Developmental Delaysmentioning
confidence: 99%